Optical and defect properties of mid-IR laser crystal Dy3+: PbGa2S4: a DFT and XPS study. Issue 28 (1st July 2022) - Yu, Xuezhou; Huang, Changbao; Ni, Youbao; Wang, Zhenyou; Wu, Haixin
Abstract : High-quality Dy 3+ :PbGa2 S4 crystals were prepared using pressure-resisted and crucible-capsule Bridgman techniques through the compensation of Ga2 S3 . Abstract : The Dy 3+ :PbGa2 S4 crystal with low phonon energy has been used to achieve direct lasing of 4.3–4.7 μm lasers. High quality PbGa2 S4 crystals are difficult to fabricate due to component volatilization. In this work, the influence of component condition on the intrinsic defects and optical absorption in the Dy 3+ :PbGa2 S4 crystal was investigated through first-principles calculations and crystal growth experiments. We found that PbGa2 S4 was prone to decompose into Ga2 S3 at its growth temperature, usually resulting in PbS-rich (Ga2 S3 -deficient) growth conditions. The calculated results of defect formation energy indicate that the PbGa and VGa defects play a dominant role in PbGa2 S4 under PbS-rich growth conditions. The Ga2 S3 -rich growth conditions can increase the defect formation energy and may lower the defect density. Our post-growth annealing and crystal growth experiments proved that the Ga2 S3 -rich conditions did improve the optical quality of the Dy 3+ :PbGa2 S4 crystal. The structure and composition of PGS were analyzed by XRD and EDS. The XRC result showed the crystal has a high crystalline quality. The changes of bond length were studied through XPS characterization and DFT calculations. The VGa and PbGa defects result in different XPS peaks of PbGa2 S4 crystals fabricated under PbS-rich and Ga2 S3 -rich growth conditions.